Drying study of an agricultural product (banana) Experimental study - Akroum, Yassine; Belhadi, Zakaria; Bensahal, Djamel (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE Département de génie mécanique, 2023)
As a result of the significant increase in global warming, the necessity of using renewable energy sources has become obvious. As a result, our attention has shifted towards harnessing solar energy, which is an abundant clean renewable resource readily available in nature. In line with this goal, we decided to use the solar thermal panels located inside the mechanical engineering workshop at the University of Al- Laghouat The purpose was to explore the possibility of using solar energy in drying perishable foodstuffs. In this regard, we conducted a study focusing in particular on bananas, a widely consumed food commodity with a highwater content of about 70%. The primary focus of the study was to investigate the effect of different levels of air flow on the efficiency of the drying process.
OPTION: Mechanical & Production Manufacturing